Strengthening The Role Of Christian Family Education For The Faith Development Of Correctional Inmates In Correctional Institution - Rantung, Djoys A.; Jura , Demsy; Vandiano, Vardik (International Journal of Science and Society, 2024)
Faith development is something very important in a person's life because through it, the level of spiritual maturity can be seen, which can have a positive influence on the life of every individual without exception. On that basis, the research title "Strengthening the Role of Christian Family Education for the Faith Development of Correctional Inmates in Correctional Institution" becomes something important to study. This research highlights the importance of the family's role in participating through Christian family education in the faith development of its family members who are inmates in a correctional institution. This qualitative research, utilizing a literature review approach, is intended to be a reference for families with members who are inmates in a correctional institution. It aims to encourage these families to participate through Christian family education in nurturing their members so that when the time comes for them to be released from the correctional institution, they are ready to live life as members of society in general.